Interaction between therapeutic interventions for Alzheimer’s disease and physiological Aβ clearance mechanisms - Morrone, Christopher; Liu, Mingzhe; Black, Sandra E.; Mclaurin, Joanne (Frontiers in Aging Neuroscience, 2015)
Most therapeutic agents are designed to target a molecule or pathway without consideration of the mechanisms involved in the physiological turnover or removal of that target. In light of this and in particular for Alzheimer’s disease, a number of therapeutic interventions are presently being developed/investigated which target the amyloid-β peptide (Aβ). However, the literature has not adequately considered which Aβ physiological clearance pathways are necessary and sufficient for the effective action of these therapeutics. In this review, we evaluate the therapeutic strategies targeting Aβ presently in clinical development, discuss the possible interaction of these treatments with pathways that under normal physiological conditions are responsible for the turnover of Aβ and highlight possible caveats. We consider immunization strategies primarily reliant on a peripheral sink mechanism of action, small molecules that are reliant on entry into the CNS and thus degradation pathways within the brain, as well as lifestyle interventions that affect vascular, parenchymal and peripheral degradation pathways. We propose that effective development of Alzheimer’s disease therapeutic strategies targeting Aβ peptide will require consideration of the age- and disease-specific changes to endogenous Aβ clearance mechanisms in order to elicit maximal efficacy.